Transport of Microplastics From the Daugava Estuary to the Open Sea - Frishfelds, Vilnis; Murawski, Jens; She, Jun (Frontiers in Marine Science, 2022)
This study considers transport of microplastics (MP) from inland waters (rivers and lakes) to coastal waters and then to open sea. A three-dimensional MP Eulerian tracer model on the basis of HIROMB BOOS model (HBM) with wave-induced transport and biofouling process is used. Multi-layer two-way nested model grids with 3-0.5-0.25-0.05 nautical mile resolution are applied to resolve relevant riverine-esturial-coastal hydrodynamics with focus on the southern waters in Gulf of Riga. The major river of Gulf of Riga, Daugava, is governed by Riga Hydro Power station (RHPS) with high daily and weekly variability of the run-off creating more intense outflows in its working hours. This gives additional complexity when calibrating this model. The model results are validated against MP observations that are collected in various cruises in summer 2018 in Gulf of Riga. There exists strong synoptic variability in the observations, which are also reproduced. As the rivers are primary source of MP, a special backtracking algorithm is developed to find the most possible source of pollutant at given location and time. Backtracking algorithm includes optimisation with respect to salinity in order to prefer trajectories coming from freshwater and consequently MP sources. Lagrangian drift studies are performed for events with high precipitation in estuary domain when sew overflow at Wastewater Treatment Plants (WWTPs) can occur, and the results are compared with different MP components in observations.